A New Theory of Taxpayer Standing - Parks, James R. (Columbia Journal of Tax Law, 2015)
Flast v. Cohen, decided by the Supreme Court in 1968, articulated a narrow exception to the general rule that merely being a taxpayer does not provide the necessary standing to challenge an expenditure of government funds alleged to violate the Constitution. Since the time of Flast, the Court has steadily narrowed the exception, retreating from the underlying rationale of the Flast decision—a trend most recently observable in the Court’s decision in Arizona School Tuition Organization v. Winn. This Note proposes a new test for taxpayer standing which aims to preserve the doctrine, while remedying some its ills. Under this Note’s proposed test, taxpayer standing is appropriate when the following three factors are met: (1) the taxpayer’s status as a taxpayer bears a reasonable relationship to the challenged expenditure of government funds in question; (2) it is of practical necessity because the political system is structurally ill-equipped to provide a remedy for those who object to a particular expenditure of government funds alleged to violate the Constitution, or the taxpayer is a member of the class for whom the especial benefit of a constitutional limitation is intended to directly run; and (3) where no other plausible party has standing to challenge the alleged violation, leaving it functionally irremediable.